Evaluation of Mtf for Fractal Optical Modulator to Znse - Abd. Al-Salam, Abdulrazak (University of Thi-Qar Journal of Science, 2019)
Optical modulator is an important component in optical system. It is a device, which changes the angle between the vision line to the target and coordinate to electrical signal. Through this study we have designed the fractal optical modulator consisting of eighteen sector, by building a computer program (SAM1) using visual basic language. In this paper assume that nine sectors one opaque and the other nine sectors are transmitted for the light. One may consider these nine sectors also as opaque for the other regions of electro-magnetic wave spectrum. For the importance of the modulation transfer function (MTF) in testing and evaluating optical systems, it becomes the dependent measurement to know the optical systems efficiency. It has been studied for optical systems with circular aperture, where that function could evaluated the image efficiency for point object in image plane at different magnitude of transmittance. In this research, the fractal optical modulator has been designed of semiconductor material by using the fractal function. Then evaluating the values of MTF at different values of refractive index and transmittance. The best modulation of Zinc Selenide (ZnSe) material optical modulator was when transmittance (T) 73%. Where the value of MTF is maximum at refractive index η λ=11.0μm (ZnSe) equal to 2.4001. The worst case of modulation was at transmittance (T) 40%. Where the value MTF is minimum at refractive index η λ=0.54μm (ZnSe) equal to 2.6754.